Pola Menyusui Ibu Postpartum di Praktek Mandiri Bidan - Suci Rahmani Nurita (Universitas Baiturrahim, 2022)
Infant morbidity rate is the second indicator in determining the health status of children because it reflects the baby's weak immune system. This is influenced by nutritional factors, socio-economic factors and demographics. Breastfeeding is related to the fulfillment of infant nutrition. Almost all infants in Indonesia (96%) have received breast milk, but infant mortality and morbidity rates are still high. It is still found in the fact that there is a tendency for postpartum mothers to discard some of the colostrum (8.9%) and throw away all of the colostrum (5.9%). There is still a dominant practice of breastfeeding (5.1%) and partial breastfeeding (55.1%) according to the situation and analysis of exclusive breastfeeding by the Indonesian Ministry of Health in 2014. This descriptive study aims to determine the pattern of breastfeeding in postpartum mothers and related factors. The population of this study were postpartum mothers (0-40 days) who had a newborn at PMB Yustati Ambarita and PMB Muzilatulnisma. The sample in this study were postpartum mothers (0-40 days) who had 27 newborns. Samples were taken by accidental sampling technique. This research was conducted from October 2020 to August 2021 at PMB Yustati Ambarita and PMB Muzilatulnisma. The results were analyzed univariately. The results showed that most of the respondents had good knowledge (74.07%), positive attitude (51.9%), high husband support (63%), high support from health workers (77.8%) and exposure to breastfeeding promotion (81.5%). A total of 96.3% of respondents had a pattern of exclusive breastfeeding for 40 days postpartum. It is hoped that the PMB will improve health education programs, especially in the lactation preparation program from the third trimester of pregnancy. It is hoped that mothers can increase their knowledge about breastfeeding preparation from trusted sources of information